PERAN GURU DALAM MENINGKATKAN KESADARAN AMALIYAH UBUDIYAH SISWA DI MADRASAH ALIYAH AL-ASY’ARI KERAS DIWEK JOMBANG - Rossa, Devind Camelia; Anshori, Sholihul (Al Tadib : Jurnal Ilmu Pendidikan, 2024)
Abstract: This article explains the role of teachers in increasing students' awareness of amaliyah ubudiyah. In this research, researchers used qualitative research with a case study type. The data obtained was through a process of observation, interviews and documentation. The existing data is then reduced, presented and then verified. The results of research that researchers have conducted show several results, namely 1). The role of the teacher in increasing awareness of ubudiyah amaliyah at Madrasah Aliyah Al-Asy'ari Keras Diwek Jombang is that the teacher always accompanies, accompanies, teaches material and practices what has been taught, motivates, gives encouragement and the teacher always advises students so that students carry out ubudiyah amaliyah activities with Good. 2). Awareness of the ubudiyah practices of students at Madrasah Aliyah Al-Asy'ari was initially still low. Students still need to be reminded every time they start an activity. As time goes by, their awareness of participating in ubudiyah amaliyah activities increases. They are no longer reminded by sat teachers about carrying out ubudiyah amaliyah activities. 3). Supporting factors for the role of teachers in increasing awareness of amaliyah ubudiyah are good madrasah policies, full support from the head of the madrasah, adequate facilities, teacher activity, teachers having abilities in the field of amaliyah ubudiyah, motivation from teachers and support from parents. Meanwhile, the inhibiting factors are ineffective use of time, lack of attention from parents, lack of practical tools, and students' varying abilities.